Islamic Counseling Program to Resolve Personal, Social, Career and Academic Problems of Students - Eko Sujadi; Muhd. Odha Meditamar; Martunus Wahab (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2020)
In spite of the legal basis for implementing guidance and counseling in higher education is not as complete and detailed as counseling services in primary and secondary education units, a number of regulations indicate that guidance and counseling services are an important element in the organization of college. This research aims to formulate a program of counseling services based on appropriate qur’ani values ​​according to the expert and describe the frequency of usage of the counseling service program to resolve student problems. This developmental research is carried out using the steps of the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of research trial consist of 3 experts and 3 product users (counselors), taken using the purposive sampling method. The analysis technique used is descriptive statistics and Kendall concordance coefficient tests. The results indicate that: (1) a counseling service program based on qur’ani values ​​is considered appropriate to be given to students; (2) the usability level of qur'ani values-based counseling service programs is considered highly usable to be used as a reference in counseling services.